2013
DOI: 10.1371/journal.pone.0066889
|View full text |Cite
|
Sign up to set email alerts
|

SERPINA2 Is a Novel Gene with a Divergent Function from SERPINA1

Abstract: Serine protease inhibitors (SERPINs) are a superfamily of highly conserved proteins that play a key role in controlling the activity of proteases in diverse biological processes. The SERPIN cluster located at the 14q32.1 region includes the gene coding for SERPINA1, and a highly homologous sequence, SERPINA2, which was originally thought to be a pseudogene. We have previously shown that SERPINA2 is expressed in different tissues, namely leukocytes and testes, suggesting that it is a functional SERPIN. To inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…Furthermore, we chose the gene encoding cytochrome B-245 β chain that is an integral part of oxidative phosphorylation and its variation has been reported in chronic granulomatous disease 30 . Serpin family member 1 (SERPINA1) encodes peptidase inhibitor clade 1, which is α-antitrypsin precursor 31 . We also chose two genes from ribosomal pathways for validation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we chose the gene encoding cytochrome B-245 β chain that is an integral part of oxidative phosphorylation and its variation has been reported in chronic granulomatous disease 30 . Serpin family member 1 (SERPINA1) encodes peptidase inhibitor clade 1, which is α-antitrypsin precursor 31 . We also chose two genes from ribosomal pathways for validation.…”
Section: Resultsmentioning
confidence: 99%
“…SERPINA2 was initially classified as a pseudogene; however, recent evidence indicates that it produces an active transcript that encodes a protein located in the endoplasmic reticulum [ 18 ]. A study that sequenced SERPINA2 genes across multiple ethnic groups indicated that in addition to active SERPINA2 protein, there is a haplotype characterized by a partial deletion which has patterns suggestive of positive selection for loss-of-function of SERPINA2 protein.…”
Section: Methodsmentioning
confidence: 99%
“…SERPINB11 , a highly conserved gene in primates, was lost and resurrected in humans where the accumulation of several mutations contributed to the appearance of a modified non-inhibitory SERPIN, probably linked to an adaptive response against the emergence of infectious diseases in recent human evolution [66] . Also, in SERPINA2 , a 90 MY old duplicate of alpha1-antitrypsin (SERPINA1), several sites seem to be under positive selection in primates, contributing to the emergence of a new advantageous function, possible as a chymotrypsin-like inhibitor [67] . Conversely, a large deletion in SERPINA2 was proposed to be selective advantageous in Africans through a potential role in fertility or in host–pathogen interactions (Seixas, et al 2007).…”
Section: Discussionmentioning
confidence: 99%